The Short Film Production by Technique Vertical Video - วีรสาร ชญานุช (Siam Communication Review, 2017)
The behavior of smartphone or tablet users nowadays is more to view objects or video vertical than horizontal. Creators are therefore producing the motion picture by applying the vertical video production technique in order to further study detail contents, kind of pictures and camera angles including its potential view and usage. The creator have also identified, after interviewing application and development production expert, that the most suitable contents for vertical video are all concerning human actions and expression Moreover, the most suitable pictures shooting is portrait regardless of the side detail, and different sizes of shots as well as its camera angles like horizontal picture. On the contrary, landscape pictures have more constrains than portrait even though most audiences prefer to watch motion picture horizontal than vertically. Plus, those traditional producers still prefer to make horizontal movies even there is a potential increasing of vertical video usage because many applications have already been launched to support vertical video function.